EVALUATION OF DYNAMIC QUALITIES OF MOVEMENT OF RE-EQUIPPED HOPPER CARS OF PILS OF LONG-TERM OPERATION (Transport systems and technologies, 2020)
As part of the work, a theoretical and experimental study (based on running dynamic tests) of the running qualities of empty hopper cars, converted from cement trucks and mineral trucks, was conducted. Computer simulation of the dynamics of empty hopper wagons converted from cement and mineral wagons depending on the condition of the track, the technical condition of the wagons and the weight of the container, the repeated presence of maximum vertical deviations and horizontal deviations of the track.A significant disadvantage of the railway transport of Ukraine is the limitation of the speed of trains with individual freight cars in an empty state, which are equipped with carts model 18-100. Among the reasons for the descent of the wheels of cars from the rails are: malfunctions of the running gear of the cars (fracture of the side frames and spring beams of the carts, malfunctions of the roller bearings of the axle box), wear of friction damper elements, unacceptable deviations and upgrades. As part of the work, a theoretical and experimental study (based on running dynamic tests) of the running qualities of empty hopper cars, converted from cement trucks and mineral trucks, was conducted. Computer modeling of the dynamics of empty hopper wagons, converted from cement and mineral wagons depending on the condition of the track, the technical condition of the wagons and the weight of the container and studies of the dependence of the wheel stability on the east.
Keywords: hopper car, tests, modeling, dynamics, derailment, technical condition, traffic safety.